The effectiveness of a peer-helping programme that increases subjective well-being. Issue 3 (27th May 2017) - Eryılmaz, Ali
ABSTRACT: The present study aims to investigate the effectiveness of a peer-helping programme in increasing the subjective well-being of a group of university students compared with a control group with the same characteristics who did not receive the intervention. The intervention recipients consisted of 13 male and 17 female participants. The peer helpers were 22 female and 8 male participants. The peer-helping programme consisted of three stages: training in helping skills, implementation and facilitating supervision sessions. The short-term effects of the programme were investigated using the Positive and Negative Affect Scale. The programme's long-term effects were evaluated using the Life Satisfaction Scale and the Positive and Negative Affect Schedule. The results indicated that the short-term subjective well-being effects of the intervention activities were statistically significant. Additionally, the results revealed statistically significant increases in positive affect and life satisfaction and significant decreases in negative affect in the intervention group compared with that in the control group. Peer-helping programme may be used to increase individuals' subjective well-being.